2007
DOI: 10.1111/j.1540-8183.2007.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Aspiration with Export Catheter in ST Elevation Myocardial Infarction

Abstract: Our study demonstrates that routine use of EXPORT catheter in patients with STEMI and coronary thrombosis is feasible, safe, and associated with significant improvements in flow-related angiographic parameters. The relative simplicity of this approach makes it an attractive option in this challenging situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…Ciszewski et al [6] showed that in their study of 137 patients with angiographic evidence of thrombus load undergoing manual thrombectomy against standard PCI, in-hospital mortality did not differ significantly, 3 vs 4% (P = 1.0) for thrombectomy vs standard PCI, respectively. A similar patient mortality rate of 4.5% from cardiac death following selective manual aspiration was found by Margheri et al [8] in 129 consecutive patients treated with the Export catheter device.…”
Section: Resultssupporting
confidence: 80%
“…Ciszewski et al [6] showed that in their study of 137 patients with angiographic evidence of thrombus load undergoing manual thrombectomy against standard PCI, in-hospital mortality did not differ significantly, 3 vs 4% (P = 1.0) for thrombectomy vs standard PCI, respectively. A similar patient mortality rate of 4.5% from cardiac death following selective manual aspiration was found by Margheri et al [8] in 129 consecutive patients treated with the Export catheter device.…”
Section: Resultssupporting
confidence: 80%
“…Likewise the following devices have all been associated with faster (lower) CTFCs: the EXPORT thrombus extraction catheter (EXPORT, Medtronic Inc., Minnesota, MN) (P = 0.0001) [71]; the PercuSurge GuardWire TM (distal protection device, Medtronic AVE) (P \ 0.01) [72,73] [76]; and finally manual thrombus aspiration using the Pronto TM extraction catheter (Vascular solutions, Minneapolis, Minnesota) before primary PCI (21.5 ± 12 vs. 17.3 ± 6) using the extraction catheter (P \ 0.01) [77].…”
Section: Ptca Versus Stentingmentioning
confidence: 98%
“…A device recently developed for percutaneous coronary intervention (PCI) is capable of aspirating blood, thrombus and plaque from the site of coronary occlusion. Aspiration therapy helps to prevent the no‐reflow phenomenon [11–14], a cause of embolization of plaque material into the microcirculation. Thus far, no one has produced an animal model to adequately approximate the rupture of atherosclerotic plaque as it occurs in humans [15].…”
Section: Introductionmentioning
confidence: 99%